AN ECONOMIC ANALYSIS OF BARLEY PRODUCTION FUNCTIONS IN WASIT PROVINCE FOR 2014 - & AL-KAISY, AL-ENIZY (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The production function of the important methods in the analysis in the components of the production process , by it can be identified the increasing in production for a given amount of resources , there for the objective of search analysis economic production functions of barley crop and knowing nature of the relationship between the factors , to fulfill the requirements of the research we are collected questionnaire from 130 farmers from crop farmers in Wasit province . We estimated by using Cobb-Douglas production function production function and restricted Cobb-Douglas. The results showed that the capital is the most influential factor in the production of barley since raised by 1% will increase production by 0.43% in a Cobb-Douglas function because the capital increase means increasing the technology used , and the factors use fall in the second stage and functions are subject to diminishing returns to scale and ealasticity replacement amounting to 0.76 indicates to the inability to intensity labour to the capital account G.Tintner test pointed to the superiority of the Cobb-Douglas unrestricted model . Also estimated the TL production function according to the random border analysis using the Frontier program , and in a way of the greatest possible ML which shows that if we increased employment by 1% , the production will increase by 0.33 and cross elasticity between labour and capital , amounting to 0.16 has shown to replacement relationship the two factors and technical effeciency at the level of the sample averaged 90% and there was no apparent effect of the acquisition . The research recommended encourage farmers to adopt improved varieties and use of resources packages with high productivity and try to stimulate the demand side of attention to livestock.